Which drugs are risk factors for the development of gastroesophageal reflux disease? - Mungan, Zeynel; Pınarbaşı Şimşek, Binnur (Turkish Journal of Gastroenterology, 2017)
Abstract Gastroesophageal reflux disease (GERD), which is common in many communities, is associated with structural factors, eating habits, and the use of certain drugs. The use of such drugs can lead to the emergence of GERD and can also exacerbate existing reflux symptoms. These drugs can contribute to GERD by directly causing mucosal damage, by reducing lower esophageal sphincter pressure (LESP), or by affecting esophagogastric motility. In this article, we report our investigation of the relationships between GERD and medications within the scope of the “Turkish GERD Consensus Group.” For the medication groups for which sufficient data were obtained (Figure 1), a systematic literature review in English was conducted using the keywords “gastroesophageal reflux” [MeSH Terms] and “anti-inflammatory agents, non-steroidal” [MeSH Terms], “gastroesophageal reflux” [MeSH Terms] and “acetylsalicylic acid” [MeSH Terms], “gastroesophageal reflux” [All Fields] and “estrogenic agents” [All Fields], “gastroesophageal reflux” [All Fields] and “progesterones” [All Fields], “gastroesophageal reflux” [All Fields] and “hormone replacement therapy” [All Fields], “gastroesophageal reflux” [MeSH Terms] and “diphosphonates” [MeSH Terms] OR “diphosphonates” [All Fields], “calcium channel blockers” [MeSH Terms] and “gastroesophageal reflux” [MeSH Terms], “gastroesophageal reflux” [MeSH Terms] and “nitrates” [MeSH Terms], “gastroesophageal reflux” [MeSH Terms] and “antidepressive agents” [MeSH Terms], “gastroesophageal reflux” [MeSH Terms] and “benzodiazepines” [MeSH Terms] and “hypnotic drugs” [MeSH Terms], “gastroesophageal reflux” [MeSH Terms] and “cholinergic antagonists” [MeSH Terms], “gastroesophageal reflux” [MeSH Terms] and “theophylline” [MeSH Terms], and “gastroesophageal reflux [MeSH Terms] AND “anti-asthmatic agents” [MeSH Terms]. The studies were analyzed and the results are presented here. Cite this article as: Mungan Z, Pınarbaşı Şimşek B. Which drugs are risk factors for the development of gastroesophageal reflux disease? Turk J Gastroenterol 2017;28(Suppl 1); S38-S43 Full Text Turkish